Principles of Qur’ānic Exegeses in Subcontinent Evolution, Diversity & Its Motives - Zafar Iqbal; Hafiz Muhammad Sajjad (Journal of Islamic and Religious Studies, 2019)
Qur’ān is the Words of Allah (SWT). Its interpretation is very difficult job because of the concept that how one can understand the will of Creator. Prophet Muhammad (SAW) was the first exegete of Qur’ān. His companions were the next one. This chain is continuously running till now. In subcontinent, translations of Qur’ān and its exegesis work started in third century Hijrah. Hundreds and Thousands of Qur’ānic exegeses exist in subcontinent in Arabic, Persian, English and Urdu languages. In subcontinent Sir Syed, Modūdī, Farahī, Shabir Uthmānī, are the big names of the field. Everyone has chosen a secluded methodology/principle to interpret the Qur’ān. These principles are known as Usūl-e-Tafsīr. There are many differences among these Usūl, due to personnel mindset and social scenario of different era. The questions that why much diversity exists in these and what are its causes, are being addressed here in this article. On the basis of analytical study, it is found that reason behind this diversity is the concept that exegesis of Quran is based on verbal traditions instead intellectual. Secondly, no one compiled these principles/methods for interpretation of Qur’ān in early centuries. In ninetieth century, due to the challenge of science and Orientalism, some scholars compiled Usūl-e-Tafsīr according to their own understanding and some insisted on traditional continuity.